Identifying Controlling Features of Engineering Design Iteration - Smith, Robert P.; Eppinger, Steven D. (Management Science, 1997)
Engineering design often involves a very complex set of relationships among a large number of coupled problems. It is this complex coupling that leads to iteration among the various engineering tasks in a large project. The design structure matrix (DSM) is useful in identifying where iteration is necessary. The work transformation matrix model developed in this paper is a powerful extension of the DSM method which can predict slow and rapid convergence of iteration within a project, and predict those coupled features of the design problem which will require many iterations to reach a technical solution. This model is applied to an automotive brake-system development process in order to illustrate the model's utility in describing the main features of an actual design process.